2022
DOI: 10.1038/s41560-022-01083-w
|View full text |Cite
|
Sign up to set email alerts
|

Size effects and active state formation of cobalt oxide nanoparticles during the oxygen evolution reaction

Abstract: Water electrolysis is a key technology to establish CO2-neutral hydrogen production. Nonetheless, the near-surface structure of electrocatalysts during the anodic oxygen evolution reaction (OER) is still largely unknown, which hampers knowledge-driven optimization. Here using operando X-ray absorption spectroscopy and density functional theory calculations, we provide quantitative near-surface structural insights into oxygen-evolving CoOx(OH)y nanoparticles by tracking their size-dependent catalytic activity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(170 citation statements)
references
References 61 publications
5
165
0
Order By: Relevance
“…Two pairs of redox peaks were observed in Figure a, that is, A1/C1 and A2/C2 at ∼1.1 and ∼1.5 V versus RHE, respectively, which would correspond to Co­(+II) ↔ Co­(+III) and Co­(+III) ↔ Co­(+IV) . However, such conventional assignment neglects associated changes in the oxygen chemical and electronic structure . In particular, a recent study revised the redox couples of Co hydroxide by operando scanning transmission X-ray microscopy and found that the peaks at ∼1.2 and ∼1.55 V versus RHE indicate Co­(+II) ↔ Co­(+III, +II) and Co­(+III, +II) ↔ Co­(+III) transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two pairs of redox peaks were observed in Figure a, that is, A1/C1 and A2/C2 at ∼1.1 and ∼1.5 V versus RHE, respectively, which would correspond to Co­(+II) ↔ Co­(+III) and Co­(+III) ↔ Co­(+IV) . However, such conventional assignment neglects associated changes in the oxygen chemical and electronic structure . In particular, a recent study revised the redox couples of Co hydroxide by operando scanning transmission X-ray microscopy and found that the peaks at ∼1.2 and ∼1.55 V versus RHE indicate Co­(+II) ↔ Co­(+III, +II) and Co­(+III, +II) ↔ Co­(+III) transition.…”
Section: Resultsmentioning
confidence: 99%
“…28 However, such conventional assignment neglects associated changes in the oxygen chemical and electronic structure. 29 In particular, a recent study 15 revised the redox couples of Co hydroxide by operando scanning transmission X-ray microscopy and found that the peaks at ∼1. The area inside the closed CV curve, shown in Figure 2a, increases during the first 30 cycles, while it remains unchanged after 50 cycles.…”
Section: Formation Of Co Oxyhydroxide On Comentioning
confidence: 99%
“…Accordingly, it is of great significance to develop earth-abundant catalysts with both high activity and electrochemical tolerance for OER. Transition metal-based catalysts are typical representatives; however, they still face the challenge of improving overall performance to meet the industrial demand. Therefore, remolding the reactivity of metal active sites (MASs) is of vital importance to realize large-scale hydrogen production via water electrolysis. One of the commonly implemented and powerful approaches is to introduce heteroatoms, such as selenium (Se), into a metal crystal lattice for efficiently modulating the electronic structure of MASs. Particularly, the Se element doped into the metal lattice usually results in metal selenide, which can significantly change the adsorption of reactive intermediates as well as reduce the OER energy barrier. Nevertheless, such catalysts easily undergo structural reconstruction and are transformed into metal oxides/hydroxides/oxyhydroxides during OER. At the same time, the instability of lattice Se leads to its massive or even complete dissolution in the electrolyte under the oxidation bias potential, thus substantially weakening the modulation effect on MASs, that is, the activation energy barrier will increase with the dissolution of functional Se (Scheme ). Moreover, large quantities of highly toxic Se-containing species dissolved from the catalysts will pollute the environment.…”
Section: Introductionmentioning
confidence: 99%
“…XPS results of Fe 2 Co 2 Ce ternary aerogels as prepared for the stability test and after the stability test: (a 1–2 ) High-resolution Co 2p: ca.782.4 and 798 eV are assigned to Co 2+ in Co 2p 3/2 and Co 2p 1/2 ; ca.780.5 and 796 eV are assigned to Co 3+ in Co 2p 3/2 and Co 2p 1/2 ; 789 and 805 eV are assigned to Co 2+ satellite peaks; and 786 and 802 eV are assigned to Co 3+ satellite peaks; ,, (b 1–2 ) High-resolution Fe 2p spectra: ca.709.7 and 723.4 eV are assigned to Fe 2+ in Fe 2p 3/2 and Fe 2p 1/2 ; ca.709.7 and 723.4 eV are assigned to Fe 3+ in Fe 2p 3/2 and Fe 2p 1/2 ; 716 and 727 eV are assigned to Fe 2+ satellite peaks; and 718 and 729 eV are assigned to Fe 3+ satellite peaks. (c 1–2 ) High-resolution O 1s spectra: ca. 535.5, 532.1, 531.3, and 530 eV, which can be assigned to water that was adsorbed (H 2 O adsorbed ), oxygen in hydroxide and oxyhydroxide­(O M–OH ), defective oxygen site (O defective ), and oxygen in metal oxide­(O M–O ), respectively. , , …”
Section: Resultsmentioning
confidence: 99%